Disharmony in the Family: How Does it Impact the Learning Process? Case Study on Senior High School Students - Gery Syehan; Hazmin Nabit Alfayadh; M. Iqbal F.A; muhammad irsyad saifullah; Muhammad Raihan Akbar (International Journal of Education and Teaching Zone, 2023)
This study aims to determine the impact experienced by children at SMA Negeri 11 Jambi City who has the potential to become victims of family disharmony (Broken Home) on their learning process. This research was conducted with a descriptive qualitative approach. Data collection was carried out using Google Forms as a media questionnaire. The data obtained is secondary data that comes directly from the research object. The population of SMAN 11 Jambi City is 837 students, but only four students can be used as research samples. This is because the researcher uses a purposive sampling technique, namely the technique of determining the research sample according to predetermined criteria to obtain results that follow this study's objectives. Based on the research that has been done, the results show that family disharmony impacts these students' learning process.